The complete book of water garden - Swindells, Philip (The Overlook Press, 1990)
Expertly written and illustrated throughout with color photos and helpful diagrams, this guide describes both traditional and modern techniques for creating a water garden. From streams, waterfalls, and fountains to self-contained features and bog gardens, every form receives in-depth coverage that is easy-to-follow. There are suggestions for siting, design, and construction; detailed assistance on stocking ponds and pools with fish and flowers; and invaluable advice on plant propagation, care, maintenance, and common problems. An extensive directory of aquatic plants covers such favorites as water lilies; floating plants (among them the beautiful, delicate water hyacinth); and many more.